Pengaruh Pemberian Pestisida Nabati Daun Bintaro (Cerbera odollam Gaertn.) terhadap Penyakit Antraknosa Tanaman Cabai (Capsicum annuum Linn.) - Rahmawati, Sri; Pramudi, Muhammad Indar; Liestiany, Elly (JURNAL PROTEKSI TANAMAN TROPIKA, 2024)
The problems that often occur with chili commodities in Indonesia every year are caused by several factors, namely changing climatic conditions, limited quality chili seed varieties and the large number of attacks by plant pests, namely pests and diseases. The main disease that always attacks chili plants is anthracnose caused by the fungus Colletotrichum capsici. Controlling vegetable pesticides is one alternative that can be done, one of which is the botanical pesticide Bintaro leaves with 2 types of solvents. This research aims to determine the effect of the botanical pesticide bintaro leaves (Cerbera odollam Gaertn.) using water and ethanol solvents in controlling anthracnose disease on chili plants (Capsicum annum Linn.). This research used a one-factor Completely Randomized Design (CRD) method consisting of 8 treatments and 3 replications, namely K = Control (No pesticide), KC = chemical pesticide (active ingredient abamectin), PA = Concentration of 10 ml bintaro leaf solution, PB = Bintaro leaf solution concentration is 20 ml, PC = Bintaro leaf solution concentration is 30 ml, PD = Bintaro leaf extract concentration is 1 ml, PE = Bintaro leaf extract concentration is 2 ml and PF = Bintaro leaf extract concentration is 3 ml. Botanical pesticide treatment of bintaro leaves on chili plants can reduce the percentage of anthracnose attacks. The highest percentage was shown in chili plants that were not treated with the botanical pesticide Bintaro leaves (55.87%). Meanwhile, the lowest percentage was in chili plants that were applied with chemical pesticides (24.20%) and in the vegetable treatment of bintaro leaves with 30 ml solution (25.97%). Apart from that, the botanical pesticide treatment of Bintaro leaves produced the highest number of fruit, namely 49923 fruit/ha, and the wet weight of the fruit was the heaviest, namely 298.92 kg/ha.